Formally modelling software architectures with the UML 2.0 profile for π-ADL. - Oquendo, Flavio (Software engineering notes.)
A key aspect of the design of any software system is its architecture. An architecture description, from a runtime perspective, should provide a formal model of the architecture in terms of components and connectors, their ports and behaviours, and how they are composed together. The Unified Modelling Language (UML) is widely used in the design of software systems and has recently been extended to better support software architecture description. This paper presents the UML 2.0 Profile for π-ADL, a novel ADL that has been designed in the ArchWare European Project. It briefly presents π-ADL and its UML 2.0 Profile, then it illustrates through a case study how the UML 2.0 Profile for π-ADL can be used for formally modelling software architectures. The toolset for supporting the UML 2.0 Profile for π-ADL is outlined: it supports architecture modelling, architectural behaviour animation, and model checking of architectural properties.